THE EFFECT OF EMOTIONAL INTELLIGENCE, COMMUNICATION AND TEAMWORK ON EMPLOYEE PERFORMANCE - Catur Widayati, C.; Arijanto, Agus; Hellen Widjaja, Purnamawati; T. Fintura, Agustina (Dinasti Publisher, 2021)
This study aims to examine and analyze the effects of emotional intelligence, communication, and teamwork on employee performance at PT XYZ. The population in this study was 50 people. The sample used was 50 respondents. The sampling method used saturated samples. Data collection Methods used survey, with the research instrument was a questionnaire. Data analysis method used Structural Equation Model (SEM) with Smart-PLS 3.3.2 analysis tool. The results showed that the emotional intelligence variable had a positive and significant effect on employee performance. Communication had a positive and significant effect on employee performance. Teamwork had a positive and significant effect on employee performance.